Necesidad de sancionar la inducción a los menores de 12 años al cometimiento de delitos sancionados con penas de reclusión. - Izquierdo, Alicia Guadalupe (2014)
This thesis entitled "Need to Punish induction under 12 years commission of offenses with imprisonment" is related to the protection that the State must provide for the children that are being used by their relatives or another in the commission of criminal acts, such as selling drugs at school, or engage in property crimes. These illegal acts should be considered as offenses and punished with severe penalties for those responsible for inducing the under twelve to commit crimes and routed their behavior in a criminal activity that harms them in their personal development, which is aimed at form into hardened criminals. The frequency with which it is taking place in the society of inducing minors in criminal acts, leading to the State passes subtract criminal policies against youth crime. The instigators knowing the insanity of less than twelve years with from criminal law and can not be punished with social and educational measures, it is done in accordance with adolescents; are used to coerce or intimidate to make crimes; this is because there is flaw in the Code of Criminal Integral in criminalizing the offense of incitement to under twelve in crime, with severe punishment for the guilty; so it was necessary to conduct a thorough legal research to propose changes to the Ecuadorian criminal regime. The theoretical, legal and doctrinal gathering, conducting surveys and interviews yielded widely recognized criteria clear and precise basis of literature, which contributed to the verification of the objectives and the testing of hypotheses regarding this practice; both the Constitution of the Republic of Ecuador guarantee humane treatment for children and adolescents; however, the Code of Criminal Integral as a typical crime does not establish the induction of children under twelve years in the commission of crimes, whose perpetrators should receive severe punishment.